2018
DOI: 10.5539/ies.v11n4p29
|View full text |Cite
|
Sign up to set email alerts
|

Defining a New 21st Century Skill-Computational Thinking: Concepts and Trends

Abstract: Computational Thinking is a skill that guides the 21th century individual in the problems experienced during daily life and it has an ever-increasing significance. Multifarious definitions were attempted to explain the concept of Computational Thinking. However, it was determined that there was no consensus on this matter in the literature and several different concepts were mentioned in the definitions found in the literature. It was considered that this fact made it difficult to understand the concept of Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 48 publications
3
35
0
3
Order By: Relevance
“…In this sense, Kalelioglu, Gülbahar and Kukul, (2016) and Valente (2019) emphasize that there is no accepted or well-known definition of CT that has been scientifically proven, as several researchers seem to perceive the concept in a slightly different way and finding a definition that every researcher agrees has been a difficult task. Haseski et al (2018) conducted a database search process in publications up to 2016, totaling 59 definitions, of which 38 were from 2011 to 2016. The analysis of this study has showed that the definition of CT uses several concepts, and resolution of problems appears 121 times; technology 53 times; thought 35; personal characteristics 16 times; operational characteristics 12; quality 10 and social characteristics 9 times.…”
Section: Computational Thinking and Mathematics Teaching In K-12mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Kalelioglu, Gülbahar and Kukul, (2016) and Valente (2019) emphasize that there is no accepted or well-known definition of CT that has been scientifically proven, as several researchers seem to perceive the concept in a slightly different way and finding a definition that every researcher agrees has been a difficult task. Haseski et al (2018) conducted a database search process in publications up to 2016, totaling 59 definitions, of which 38 were from 2011 to 2016. The analysis of this study has showed that the definition of CT uses several concepts, and resolution of problems appears 121 times; technology 53 times; thought 35; personal characteristics 16 times; operational characteristics 12; quality 10 and social characteristics 9 times.…”
Section: Computational Thinking and Mathematics Teaching In K-12mentioning
confidence: 99%
“…The adoption of Computational Thinking (CT) ideas and programming teaching in K-12 schools can be found in national and international programs and initiatives (Barr & Stephenson, 2011;Guzdial, 2008;Haseski, Ilic & Tugtekin, 2018;Kong & Abelson, 2019;Royal Society, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of late, many scholars and practitioners have raised the imperative of having a well-developed CT skill among students. In this regard, [1] assert that students in this century need to possess sound CT skill in dealing with more challenging problems compared to those in earlier centuries. In other words, the imperative for such a skill has grown significantly, given the complexities of today's life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [12] carried out a study in which they found that CT scores correlated strongly with general academic success, thus they concluded that such a skill could be used as an early indicator and predictor of academic success. Spurred by the promising, interesting findings of a study by [1], new methods and techniques for integrating CT into existing curricula have been proposed to help students develop CT skill, encompassing all levels of education, from the pre-school to the university. In particular, they suggested that several activities could be developed and applied to public schools for students of different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Computational thinking is the everyday living skills needed by everyone, not just programming skills used commonly by computer scientists (Wing, 2006(Wing, , 2008. According to (Haseski, Ilic, & Tugtekin, 2018), computational thinking is an important part of learning in the 21 st century. (Weintrop et al, 2016) assigned 10 initial skills in computational thinking that must be taught in school.…”
Section: Introduce the Problemmentioning
confidence: 99%